A WSN based System for Enhancing Intra Mobility Solution for Healthcare – A Review - Suryawanshi, Chandani R; Bhute, Yogesh C (International Journal of Computer Sciences and Engineering, 2014)
Currently, several solutions are available for monitoring patient health using body sensors. In hospitals, healthcare wireless sensor networks (HWSNs) offer support to access these sensors to allow for continuous patient monitoring. In order to improve the quality-of-life of hospitalized patients, it is important to let them walk around the monitored area. This ability brings several challenges to HWSNs with mobility support. Due to the crucial importance of the sensed parameters the HWSNs must be in continuous communication with the body sensors. The connection between body sensors and a healthcare wireless sensor network is performed through an access point. Indoor communications are limited in terms of signal propagation and, therefore, several access points to cover large areas are deployed. In order to maintain the sensor’s accessibility these should frequently change their point of attachment by performing a mechanism known as a handover. Handover mechanisms are able to support the intra-mobility of sensors in networks within the same domain. This paper surveys the most recent intra-mobility solutions with special focus on handover approaches that can be used in healthcare wireless sensor networks. An in depth review of the related literature is performed in order to present the state of the art on this topic, to discuss the available solutions, and to point out open issues for further research work. In healthcare scenarios it is important that technology maybe focused on the patients’ quality-of-life. The use of HWSNs improves patients’ health monitoring. These technologies can be used for patient monitoring in both a real-time and continuous manner. When hospitalized, the patients should be autonomous and their mobility should be preserved whenever possible. That way the HWSNs should support this mobility and ensure continuous patient monitoring.